Tantangan dan Peran Insinyur Mesin dalam Perkembangan Revolusi Industri 4.0 di Indonesia - hidayat, nur afif (Maliki Interdisciplinary Journal, 2025)
The development of science and technology has brought all countries in the world into a new era called industrial world 4.0. The era’s revolution seems to attract the interest of all countries to prepare themselves to face important developments related to the industrial world 4.0. Preparing knowledgeable and reliable human resources is something that is being done by many countries, including Indonesia. In mechanical engineering, one of the problems in mechanical engineering is the challenges and role of a mechanical engineer in the development of the Industrial Revolution 4.0 in Indonesia. Success in discussing the industrial world 4.0 cannot be separated from the role of a mechanical engineer in advancing it. A mechanical participant must want to be part of and understand the challenges faced by the mechanical field in transitioning to the world of industry 4.0. Ships are an example of where the mechanical profession can work, because there are mechanical components on ships. The role of a mechanical engineer is very important in the world of industry 4.0